2016
DOI: 10.1007/s10948-016-3752-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel Quaternary Dilute Magnetic Semiconductor (Ga,Mn)(Bi,As): Magnetic and Magneto-Transport Investigations

Abstract: Magnetic and magneto-transport properties of thin layers of the (Ga,Mn)(Bi,As) quaternary dilute magnetic semiconductor grown by the low-temperature molecular-beam epitaxy technique on GaAs substrates have been investigated. Ferromagnetic Curie temperature and magneto-crystalline anisotropy of the layers have been examined by using magneto-optical Kerr effect magnetometry and low-temperature magneto-transport measurements. Post-growth annealing treatment of the layers has been shown to enhance the hole concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Increasing the In content decreases the band gap of the (In,Ga,Mn)As quaternary semiconductor (from about 1.5 to 0.4 eV for In compositions between 0% and 100%, respectively) and affects the magnetic easy axis direction [26]. In addition, a range of unusual magnetic effects have been reported for (In,Ga,Mn)As [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the In content decreases the band gap of the (In,Ga,Mn)As quaternary semiconductor (from about 1.5 to 0.4 eV for In compositions between 0% and 100%, respectively) and affects the magnetic easy axis direction [26]. In addition, a range of unusual magnetic effects have been reported for (In,Ga,Mn)As [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitatively similar behaviour has been registered for the Hall-bar of the reference (Ga,Mn)As layer, displaying, however, significantly smaller amplitude of the PHE resistivity changes and the transitions between their low and high values occurring at much smaller values of magnetic field, corresponding to smaller values of coercive fields in (Ga,Mn)As; c.f. [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our early measurements, performed by means of a modulation photoreflectance spectroscopy method [ 6 ], revealed that an addition of only 0.3% Bi atoms substituting As atoms in the (Ga,Mn)As crystal lattice caused a distinct modification of its valence band [ 1 ]. Moreover, it results in a significant increase in the magnitude of magnetotransport effects, as evidenced by our recent experiments performed for (Ga,Mn)(Bi,As) layers containing up to 1% Bi atomic fraction [ 7 , 8 ]. The enhanced spin–orbit interaction is especially favourable for spintronic materials as it enables one to electrically tune the magnetization direction through the spin–orbit torque effect [ 9 ].…”
Section: Introductionmentioning
confidence: 94%
“…This is caused by a strong enhancement of the strength of spin-orbit coupling resulting from the replacement of As atoms by much heavier Bi atoms, leading to a large relativistic correction to the GaAs band structure 13,14 . First reports on magnetic properties of (Ga,Mn)(Bi,As) epitaxial layers displayed their similarity to those of (Ga,Mn)As ones with somewhat lower T C 12,15 .…”
Section: Introductionmentioning
confidence: 93%
“…Both concepts allow achieving new type of non-volatile memory elements, in which a bit of information can be written magnetically and read electrically. The output signal in such devices can be increased by addition of a small fraction of bismuth into (Ga,Mn)As, which enhances the magneto-transport effects in the quaternary (Ga,Mn)(Bi,As) compound, as demonstrated recently 11,12 . This is caused by a strong enhancement of the strength of spin-orbit coupling resulting from the replacement of As atoms by much heavier Bi atoms, leading to a large relativistic correction to the GaAs band structure 13,14 .…”
Section: Introductionmentioning
confidence: 95%